2013
DOI: 10.1038/npp.2013.173
|View full text |Cite
|
Sign up to set email alerts
|

The Speed of Cocaine Delivery Determines the Subsequent Motivation to Self-Administer the Drug

Abstract: The rapid delivery of drugs of abuse to the brain is associated with an increased likelihood and severity of addiction. Here we evaluated the hypothesis that rapidly delivered cocaine facilitates the addiction process by promoting the development of enhanced motivation for the drug. Rats lever-pressed for cocaine delivered intravenously over 5 or 90 s under fixed ratio (FR) during 6-h sessions. The motivation for cocaine was subsequently assessed using a progressive ratio (PR) schedule, where each successive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
(96 reference statements)
5
21
0
Order By: Relevance
“…A notable exception is Mantsch et al (2004), who showed that escalation occurs earlier at higher doses (2 versus 0.5 mg/kg/injection). This is in line with a number of studies that have failed to see escalation of cocaine intake at lower drug doses (0.25-0.6 mg/kg/injection) (Ferrario and Robinson, 2007, Kippin et al, 2006, Mantsch et al, 2004and Minogianis et al, 2013. Escalation is also facilitated by a rapid speed of cocaine onset.…”
Section: Bsupporting
confidence: 88%
See 3 more Smart Citations
“…A notable exception is Mantsch et al (2004), who showed that escalation occurs earlier at higher doses (2 versus 0.5 mg/kg/injection). This is in line with a number of studies that have failed to see escalation of cocaine intake at lower drug doses (0.25-0.6 mg/kg/injection) (Ferrario and Robinson, 2007, Kippin et al, 2006, Mantsch et al, 2004and Minogianis et al, 2013. Escalation is also facilitated by a rapid speed of cocaine onset.…”
Section: Bsupporting
confidence: 88%
“…However, a more recent study suggests that this lack of effect might be restricted to the initial stages of drug self-administration (the first 3-4 sessions following acquisition of the drug self-administration task). Bouayad-Gervais et al (2014) showed that, consistent with prior studies (Crombag et al, 2008, Minogianis et al, 2013and Wakabayashi et al, 2010, varying the speed of i.v. cocaine injection (5 or 90 s) has no effect on intake during the first 3-4 self-administration sessions.…”
Section: Pharmacokinetic Variables Influence Drug-taking (Consummatorsupporting
confidence: 57%
See 2 more Smart Citations
“…administration experiments were based on used faster pumps that delivered 1.6 ml/minute [95], compared to ours that infuse drug at approximately 1.0 ml/minute. The relatively slow speed of the self-administration pumps could have lowered the efficacy of the cocaine delivery system, as faster speeds of delivery results in increased motivation during self-administration in rats [120,121] and humans [122,123]. This explains why all routes of cocaine absorption used by humans facilitate concentrated, rapid delivery of concentrated drug doses into the bloodstream [124,125].…”
Section: Discussionmentioning
confidence: 99%